TINJAUAN PUSTAKA TENTANG BROMHIDROSIS - Febbi Anggi (Jurnal Medika Hutama, 2024)
In bromhidrosis, biotransformation of odorless natural secretions into volatile odorous molecules occurs and is closely related to excessive sweating. The distribution of Corynebacterium species also differs among different age groups. Bromhidrosis is more common in men because the number of Corynebacterium in men is higher than in women. However, the Corynebacterium species found differ between the two genders. Sweat is a secretory fluid that routinely moistens human skin and provides skin protection through at least peptide components and antibacterial salts. Staphylococcus spp. have a variable distribution in different age groups. Apocrine bromhidrosis is the most common form of bromhidrosis. BTX A can denervate the apocrine glands by inhibiting the release of acetylcholine, which is a neurotransmitter from the sympathetic nerves that innervate the apocrine glands. Microwave therapy is indicated in patients who have bromhidrosis accompanied by hyperhidrosis.